1993
DOI: 10.1002/cne.903340407
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of prosaposin‐like immunoreactivity in rat brain

Abstract: Prosaposin is the precursor for saposins A, B, C, and D, which are small lysosomal proteins required for the hydrolysis of sphingolipids by specific lysosomal hydrolases. With a monospecific anti-saposin C antibody, which cross-reacts with prosaposin but not with saposin A, B, or D, the present immunoblot experiments showed that the rat brain expresses an unprocessed approximately 72 kDa protein (possibly prosaposin) and little saposin C. Regional analysis demonstrated that prosaposin is abundant in the brains… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
32
1

Year Published

1994
1994
2007
2007

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 46 publications
(37 citation statements)
references
References 27 publications
4
32
1
Order By: Relevance
“…Importantly, the neurite outgrowth effects are cell-specific because NS20Y, a cholinergic neuroblastoma cell line, responded better than Neuro2A, a noncholinergic cell line (23). This is consistent with the localization of prosaposin, as opposed to the individual saposins, to cholinergic neurons in rat brain (37). These results imply that the prosaposin-mediated neurotrophic effects, via its saposin C segment, may be mainly in specific sets of neurons.…”
supporting
confidence: 78%
“…Importantly, the neurite outgrowth effects are cell-specific because NS20Y, a cholinergic neuroblastoma cell line, responded better than Neuro2A, a noncholinergic cell line (23). This is consistent with the localization of prosaposin, as opposed to the individual saposins, to cholinergic neurons in rat brain (37). These results imply that the prosaposin-mediated neurotrophic effects, via its saposin C segment, may be mainly in specific sets of neurons.…”
supporting
confidence: 78%
“…Immunocytochemical studies using a prosaposinspecific antibody demonstrated high concentrations of prosaposin in human cortical neurons (unpublished data). A similar survey in rat brain demonstrated widespread prosaposin immunoreactivity in neurons (9). Total prosaposin deficiency in humans due to a point mutation in the start codon of the prosaposin gene (24) resulted in severe neurological deterioration evident at birth with prominent cortical hypomyelination and cerebral atrophy (25).…”
Section: Discussionmentioning
confidence: 98%
“…In addition to its role as a lysosomal precursor, prosaposin is presumed to have additional functions, since it exists as a secretory protein in human milk, cerebrospinal fluid, and seminal plasma (3)(4)(5); it is present in unprocessed form in high concentrations in human (6) and rat (7) brain; its mRNA is abundant in brain and dorsal root ganglia during embryonic development (8); it is present predominantly in neurons after immunostaining (9); and it occurs as an integral membrane component (10).…”
mentioning
confidence: 99%
“…Prosaposin can also be found in many biological fluids such as seminal plasma, human milk, and cerebrospinal fluid (reviewed in [120]). Prosaposin is abundant in the brain where it is localized exclusively in certain neurons [121]. Its presence on the neuronal surface was first reported by Fu and colleagues in 1994 [122] and since then many functions have been attributed to the secreted form of prosaposin.…”
Section: Prosaposin Is a Potential Catalyst Of Ganglioside Shedding Amentioning
confidence: 99%